2021
DOI: 10.1007/s10489-021-02217-5
|View full text |Cite
|
Sign up to set email alerts
|

Covariance matrix forecasting using support vector regression

Abstract: Support vector regression is a promising method for time-series prediction, as it has good generalisability and an overall stable behaviour. Recent studies have shown that it can describe the dynamic characteristics of financial processes and make more accurate forecasts than other machine learning techniques. The first main contribution of this paper is to propose a methodology for dynamic modelling and forecasting covariance matrices based on support vector regression using the Cholesky decomposition. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…where 𝐻𝐻 𝑃𝑃 and 𝐿𝐿 𝑃𝑃 are the daily high and low prices, respectively. More details about the applied range-based covariance estimator and its properties can be found in Fiszeder and Orzeszko (2021), who employ this estimator in a new methodology for dynamic modeling and forecasting covariance matrices based on support vector regression.…”
Section: Range-based Covariance Estimator For Exchange Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…where 𝐻𝐻 𝑃𝑃 and 𝐿𝐿 𝑃𝑃 are the daily high and low prices, respectively. More details about the applied range-based covariance estimator and its properties can be found in Fiszeder and Orzeszko (2021), who employ this estimator in a new methodology for dynamic modeling and forecasting covariance matrices based on support vector regression.…”
Section: Range-based Covariance Estimator For Exchange Ratesmentioning
confidence: 99%
“…Fischer et al, 2019). These factors cause machine learning algorithms to outperform most traditional stochastic methods in financial market forecasting (Fiszeder & Orzeszko, 2021;Ryll & Seidens, 2019). The most popular ML approaches in the field of finance are Artificial Neural Network (ANN) and Support Vector Machine (SVM).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several decades, significant progress has been made in modelling the volatilities of multivariate stock market returns. Nowadays, there are four main approaches: multivariate generalised autoregressive conditional heteroskedasticity (MGARCH) models (Engle, 2002;Engle and Kroner, 1995), multivariate stochastic volatility (MSV) models (Chib et al, 2009) realised covariance models (Bollerslev et al, 2018;Jin and Maheu, 2013), and machine learning (ML) algorithms (Bejger and Fiszeder, 2021;Fiszeder and Orzeszko, 2021). All of these approaches have some strengths and weaknesses, and the choice between them depends on the specific characteristics of the data, the objectives of the analysis, and the trade-offs between modelling flexibility and computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…It is designed to have a good power of generalization and an overall stable behavior, which implies a good out-of-sample performance. Many studies in the literature have shown that SVR models can give more accurate forecasts than alternative machine learning methods and can be successfully used to forecast financial time series, such as stock indices, stock prices, future contracts, or exchange rates (see, e.g., [32][33][34][35]). SVR and SVR-based models have also been applied to forecast crude oil prices [36][37][38][39][40][41] or exchange rates [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%